Q-learning based handoff algorithm for satellite system with ancillary terrestrial component - Dan-ni XIONG; Yi LI (Tongxin xuebao)
In the integrated satellite-terrestrial communication system,i.e.,mobile satellite system with ancillary terres-trial component (MSS-ATC),the long transmission delay of satellite link was a huge challenge which may lead to high handoff dropping probability.In order to address this problem,a novel handoff decision strategy was proposed based on the predictive RSS and Q-learning algorithm.Extensive simulation results demonstrate that the proposed scheme can de-crease the handoff dropping probability,reduce the unnecessary handoff times and maximize the network reward.In ad-dition,the proposed scheme can also adapt to the situation of high-speed movement very well.